Competitive adsorption of N2 and CO2 on coal by a self-balancing triaxial equipment: A case study. Issue 1 (11th April 2023) - Xue, Yang; Wang, Hanpeng; Shi, Shaoshuai; Xing, Jiapeng; Wang, Peng; Zheng, Ruijie; Yu, Xinping
ABSTRACT: A self-balancing coal triaxial loading adsorption-desorption-replacement tester was independently developed to investigate the influence of in-situ stress on the competitive adsorption of a N2 and CO2 mixture while providing guidance for coal seam gas injection and extraction. A binary gas mixture of N2 (20%) and CO2 (80%) was prepared using a high-pressure gas distribution system. The isothermal competitive adsorption and desorption experiments of the binary mixed gas under different stress states (6 MPa, 9 MPa, 12 MPa, 15 MPa) were performed on the coal samples from Xinzhuangzi coal mine, Huainan. The results showed that when the confining pressure remained unchanged and the adsorption equilibrium pressure was 0.6 MPa, the axial pressure increased from 6 MPa to 12 MPa (the stage before coal yielded), the coal adsorption capacity for N2 and CO2 decreased, and the competitive adsorption capacity of N2 decreased by 14.4%. When the axial pressure increased from 12 MPa to 15 MPa (after the coal yielded), the coal adsorption capacity for N2 and CO2 increased, and the competitive adsorption capacity of N2 increased by 22.3%. When the stress remained unchanged, the adsorption equilibrium pressure increased, adsorption growth rate of N2 was greater than that of CO2, and competitive adsorption capacity of N2 was enhanced. Therefore, in the coal pre-yield stage, the CH4 -displacement ability of the mixed gas decreased with an increase in stress and increased with an increase in air pressure. This phenomenon indicates that low stress and high gas pressure promoted the replacement of CH4 by the mixed gas and increased the permeability of the low-permeability coal seam. Beyond the yield point of the coal, the addition of N2 promoted the replacement of CH4 by gas injection; the addition also promoted the permeability enhancement of the coal seam. Thus, the amount of N2 in the mixed gas should be increased as in-situ stress increases.This research can contribute to CO2 recovery and energy exploitation and utilization.